PENGARUH INFLASI, HARGA MINYAK MENTAH INDONESIA, DAN SUKU BUNGA (BI RATE) TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) (DATA PER BULAN PERIODE 2006-2012) - Novitasari, Istriyansah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The investors in making investment will seek to invest in shares of companies that can provide a return or gains and dividends could be or capital gains. The investment activity in the stock market. Capital market participants will observe the movement of the Composite Stock Price Index (IHSG) on the stock exchange as one of their decision to invest. IHSG is influenced by several factors such as the price of Crude Oil Indonesia, Inflation and Interest Rates (BI Rate). The purpose of this research study was to examine the influence of Indonesian Crude Oil Prices, Inflation and Interest Rates (BI Rate) of the Composite Stock Price Index (IHSG) partially. This study took a case study in Indonesia during the period 2006 to 2012. Keywords: Composite Stock Price Index (IHSG), Indonesian Crude Oil Prices, Inflation and Interest Rates (BI Rate).